Santai Ilmu Publication Employee Management System - Ahmad Rosman, Aina Razita; Mohd Nawi, Nazri (Applied Information Technology And Computer Science, 2025)
This project emphasizes and concerns in maintaining employee data for a web-based solution to solve data lost issues as well as data maintanence. Administrators will be able to input employee data and control attendance using the proposed system, while workers will be able to check their attendance performance and obtain salary statements online. The project also emphasizes the need of implementing a payroll system that allows employees to view their pay stubs online which reducing the need for paper-based statements and improving employee access to information. The project's scope includes a web-based personnel administration system for administrators to use for HR functions such as time and attendance monitoring and payment. The report also contains a list of personnel participating in the information retrieval process as well as system users, as well as a list of system function modules. The anticipated result is a fully functional software solution for managing corporate tasks such as staff attendance records and payroll statements, with a user-friendly interface that allows easy access to the system's features and functions.